Tora Chira Bihu : A Pre Bihu Celebration Of The Thengal Kachari Tribe In Assam (Journal of Namibian Studies : History Politics Culture, 2023)
Most, if not all, of the societies of the world periodically set aside portions of time for celebration. These are moments of special significance to the group or community. They may be moments of transition, from one season to another or from one stage of life to another. , These recurring moments of special significance , with the celebrations that fill them, are called festivals.  Festival is a prime device for promoting social cohesion, for integrating individuals into a society or group and maintaining them as members through shared, recurrent, positively reinforcing performance.( Smith 1972). Festivals are a part of traditional culture. Their nature is determined by both season and religion. Further, tradition is never static. With the change in lifestyle of the people, customs and beliefs are also tending to get changed.( Goswami 1995). The above stated opinions regarding festivals and celebrations depict that the traditional festivals help in building cohesion and solidarity among the participants of the community.Hence this paper will make an attempt to explore the significance of the celebration of ‘Tora Chira ‘ Bihu among the The Thengal Kachari Tribe in Assam.